Olivia and the fairy princesses - Falconer, Ian, 1959- (New York : Atheneum Books for Young Readers, 2012)
"Olivia is having an identity crisis! There are too many ruffly, sparkly princesses around these days, and Olivia hashad quite enough. She needs to stand out! She has to be special!"--Provided by publisher.
Booklist
Pub Weekly
School Library Journal
Booklist, August 2012
Kirkus Review, July 2012
Pub Weekly, June 2012
Keywords: Individuality -- Juvenile fiction; Olivia (Fictitious character : Falconer) -- Juvenile fiction; Princesses -- Juvenile fiction; Swine -- Juvenile fiction; Individuality -- Fiction; Olivia (Fictitious character : Falconer) -- Fiction; Pigs -- Fiction; Princesses -- Fiction; Individuality -- Fiction; JUVENILE FICTION / Animals / Pigs; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Imagination & Play; Olivia (Fictional character : Falconer) -- Fiction; Pigs -- Fiction; Princesses -- Fiction; Picture books for children